PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN DENGAN REPUTASI PERUSAHAAN SEBAGAI PEMODERASI - RIYANTI; ZIKRA SUPRI; SULTAN (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2021)
This aim of this research is to analyze the effect of corporate social responsibility disclosure on financial performance with the company's reputation as the moderating variable. The population of this research consisted of 20 state-owned companies (BUMN) listed in the Indonesia Stock Exchange (IDX). This sample was selected using purposive sampling technique consisting of 16 companies with observation years, i.e. 2015-2020. The data were analyzed using Moderated Regression Analysis (MRA).The results showed that disclosure of corporate social responsibility had an effect on financial performance and company reputation was able to moderate the relationship between disclosure of corporate social responsibility and financial performance.